On value and abstract labour: A reply to Werner Bonefeld - Kicillof, Axel (2011)
This article offers a reply to Werner Bonefeld's recent contribution to the debate on value and abstract labour, in which he critically engages with our previous articles dealing with these questions. We argue that Bonefeld's criticisms are not simply based on disagreements over these controversial issues, but also on a misunderstanding of our stance on abstract labour and value. In addition to clarifying our position, the article provides some brief critical remarks on Bonefeld's own intervention in the debate and shows that his contribution fails to offer a solid analysis of the fundamental categories of the critique of political economy.